Design of Arduino based home automation systems incorporating identity detection - Islam, Md. Wasif; Roy, Bishwajit; Preety, Nazia Homaira; Mahtab, Farhan Bin (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.